A musicoterapia como estratégia de cuidado ao sofrimento relacionado ao trabalho - Pinho, Flavia de Oliveira (2021)
This dissertation aims to investigate and describe the contributions of Music Therapy in the care of work-related suffering. To this end, we used the case of a worker from a Service for Assistance to Victims of Violence in the city of São Paulo, who has participated in a Music Therapy intervention carried out with a team of service professionals during 2017, among March and July, in thirteen weekly meetings lasting an hour and a half. To analyze the effects of this intervention, the case study had the worker’s participation in the meetings. In addition, an interview, which sought to investigate how she signifies the effects and consequences of this experience in the face of the suffering experienced at work, was conduced. The investigation relates the areas of Social Psychology, more specifically the contributions related to the field of workers' health, and Community and Social Music Therapy. Through the perspective of Social Psychology work was defined, the essential dimension that constitutes human life, as loaded with innumerable meanings, being an activity from which one finds personal fulfillment and recognition in society. Community Music Therapy enabled listening to how the workers deal with their day to day work, very marked by the issue of violence, giving voice, autonomy and strengthening them collectively. The data were formed considering the relationship between the worker subject of research and as participants in the group and the meanings related to work. The analysis was divided into two large groups, the first one was the sound-musical analysis and the second one attempted to identify a relationship between working conditions and health, presenting the consequences of the intervention in Music Therapy. In this second set, two major themes were identified based on the discourse of the research subject worker and the meeting process: group work and precarious work as a source of suffering. It was concluded that the intervention in Music Therapy, can be an excellent strategy to give voice to the workers, to increase the group’s strength, to generate new ways of being and living, creating community aesthetics and new possibilities for constituting subjectivity